Enhanced piezoelectricity of a PVDF-based nanocomposite utilizing high-yield dispersions of exfoliated few-layer MoS2. Issue 9 (15th June 2019) - Jiang, Lingqing; Xie, Haian; Hou, Yan; Wang, Shan; Xia, Yushuang; Li, Yang; Hu, Guo-Hua; Yang, Quanling; Xiong, Chuanxi; Gao, Zhaodongfang
Abstract: Piezoelectric polymer composite films have attracted extensive attention due to their comprehensive characteristics such as low cost, good flexibility, mechanical property and excellent processability. Among the known polymers, poly (vinylidene fluoride) (PVDF) is an ideal piezoelectric polymer because the β -crystalline form of PVDF has the highest polarization per unit cell. However, initial PVDF mostly suffers from the lack of a β phase, restricting its potential applications. Few-layer MoS2 is predicted to be strongly piezoelectric owing to the opposite orientations of adjacent atomic layers. In this work, we report an efficient approach to enhance the piezoelectric property of PVDF-based nanocomposites by combining few-layer MoS2 with PVDF. The product yield for few-layer MoS2 reached a value as high as 83.3% via a unique liquid-exfoliation technique. For a few-layer MoS2 /PVDF composite film with 1 wt.% few-layer MoS2, a high piezoelectric performance enhancement of 360% was achieved compared with the initial PVDF film. In addition, due to the intrinsic lubrication of MoS2, the highest elongation of the piezoelectric composite film was found to be four times higher than that of the pure PVDF film.